Visualizing Presynaptic Calcium Dynamics and Vesicle Fusion with a Single Genetically Encoded Reporter at Individual Synapses - Jackson, Rachel E.; Burrone, Juan (Frontiers in Synaptic Neuroscience, 2016)
Synaptic transmission depends on the influx of calcium into the presynaptic compartment, which drives neurotransmitter release. Genetically encoded reporters are widely used tools to understand these processes, particularly pHluorin-based reporters that report vesicle exocytosis and endocytosis through pH dependent changes in fluorescence, and genetically encoded calcium indicators (GECIs) that exhibit changes in fluorescence upon binding to calcium. The recent expansion of the color palette of available indicators has made it possible to image multiple probes simultaneously within a cell. We have constructed a single molecule reporter capable of concurrent imaging of both presynaptic calcium influx and exocytosis, by fusion of sypHy, the vesicle associated protein synaptophysin containing a GFP-based pHluorin sensor, with the red-shifted GECI R-GECO1. Due to the fixed stoichiometry of the two probes, the ratio of the two responses can also be measured, providing an all optical correlate of the calcium dependence of release. Here, we have characterized stimulus-evoked sypHy-RGECO responses of hippocampal synapses in vitro, exploring the effects of different stimulus strengths and frequencies as well as variations in external calcium concentrations. By combining live sypHy-RGECO imaging with post-hoc fixation and immunofluorescence, we have also investigated correlations between structural and functional properties of synapses.